Analysis of the relationship between attitudinal factors and the intention to purchase remanufactured products - Reis, Felipe; Fortes, Raísa; Paza, Andrei Carlos; Brandao, Danielle; Grandolpho, Bernadete Lourdes (Revista de Administração da UFSM, 2020)
Purpose – Remanufacturing is an essential strategy for implementing the concepts of the circular economy, but consumers must be willing to consume remanufactured products for this strategy to be successful. This study analyzes how the attitudinal factors environmental knowledge, environmental awareness, attitude towards sustainable products and perceived effectiveness by consumers influence the intention to purchase remanufactured products in the Brazilian market. Design/methodology/approach – A descriptive research with quantitative methodology was developed with a sample of 289 participants, the analysis of the results was made using the statistical method of multiple linear regression. As limitations of the study, we can mention the sampling for convenience that restricts the generalization of the results. Findings – The results indicate that the four attitudinal factors analyzed influence the intention to purchase remanufactured products. This article presents theoretical and practical contributions. Research limitations/implications – From a theoretical point of view, this study allows a better understanding of the factors related to the intention to purchase remanufactured products by Brazilian consumers; from a practical point of view, this study provides a better understanding of the characteristics of the consumer market for remanufactured products, and can assist in the development of sustainable actions by companies. Originality/value – This article is the first study that seeks to identify and analyze factors that influence the intention to purchase remanufactured products in Brazil and can assist organizations in implementing the circular economy more effectively.